Overview of US Agricultural Trade with China - Xiuzhi Wang; Edward A. Evans; Fredy H. Ballen (EDIS)
One bright spot in the US–China trade deficit is the trade of agricultural products, which continues to reflect a trade surplus that has grown considerably within the last decade. This 11-page fact sheet provides an overview of US–China trade of agricultural products, with special focus on produce, specifically over the period 2000 to 2010, and to highlight the main factors driving the widening of the agricultural trade surplus. The implications of modernizing the Chinese agricultural sector for the US fruit and vegetable industry are also discussed. Written by Xiuzhi Wang, Edward A. Evans, and Fredy H. Ballen, and published by the UF Department of Food and Resource Economics, February 2012.